KEMAMPUAN KONEKSI MATEMATIS DITINJAU DARI KEYAKINAN DIRI DENGAN MODEL PEMBELAJARAN POGIL - Suri, Indah Resti Ayuni (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
The abstract should reflect the overall substance of the article and be able to help the reader This study aims to determine the effect of the Process Oriented Guided Inquiry Learning (POGIL) model and the level of self-efficacy on students’ mathematical connection ability. The problem addressed in this research is the low level of students’ mathematical connection ability and the lack of optimal learning models that support its development. This research employed a quantitative method with a quasi-experimental design, specifically the posttest-only control group design. The sample consisted of two randomly selected eighth-grade classes at SMP Negeri 2 Bandar Lampung, designated as the experimental and control classes. The instruments used were a mathematical connection ability essay test and a self-efficacy questionnaire. Data analysis was carried out using two-way ANOVA at a 5% significance level. The results indicated that the POGIL learning model had a significant effect on students’ mathematical connection ability, with a significance value of 0.000 < 0.05. Similarly, the level of self-efficacy also significantly affected students’ mathematical connection ability, with a significance value of 0.000 < 0.05. However, there was no significant interaction between the POGIL model and the level of self-efficacy on students’ mathematical connection ability, as indicated by a significance value of 0.840 > 0.05. Therefore, it can be concluded that both the POGIL model and self-efficacy independently contribute to enhancing students’ mathematical connection ability. These findings are expected to serve as a reference for selecting effective and adaptive instructional strategies based on students’ affective characteristics. ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Process Oriented Guided Inquiry Learning (POGIL) dan tingkat keyakinan diri terhadap kemampuan koneksi matematis peserta didik. Permasalahan yang diangkat adalah rendahnya kemampuan koneksi matematis serta kurang optimalnya model pembelajaran yang mendukung pengembangan aspek tersebut. Penelitian ini menggunakan metode kuantitatif dengan desain eksperimen semu (quasi-experimental design) berupa posttest-only control group design. Sampel terdiri dari dua kelas yang dipilih secara acak dari kelas VIII di SMP Negeri 2 Bandar Lampung, masing-masing sebagai kelas eksperimen dan kontrol. Instrumen penelitian berupa tes uraian kemampuan koneksi matematis dan angket keyakinan diri. Analisis data dilakukan menggunakan uji ANOVA dua arah pada taraf signifikansi 5%. Hasil menunjukkan bahwa model pembelajaran POGIL berpengaruh signifikan terhadap kemampuan koneksi matematis peserta didik dengan nilai signifikansi 0,000 < 0,05. Demikian pula, tingkat keyakinan diri berpengaruh signifikan terhadap kemampuan koneksi matematis dengan nilai signifikansi 0,000 < 0,05. Namun, tidak ditemukan interaksi yang signifikan antara model pembelajaran POGIL dan tingkat keyakinan diri terhadap kemampuan koneksi matematis karena nilai signifikansi sebesar 0,840 > 0,05. Dengan demikian, dapat disimpulkan bahwa model POGIL dan keyakinan diri masing-masing berkontribusi secara mandiri dalam meningkatkan kemampuan koneksi matematis peserta didik. Hasil penelitian ini diharapkan dapat menjadi acuan dalam memilih strategi pembelajaran yang efektif dan adaptif terhadap karakteristik afektif siswa.